Предмет: Математика,
автор: dondosupermider
найдите x (x-3)^4 - 5(x-3)+6=0
Приложения:
![](https://files.topotvet.com/i/4bb/4bb461177599c1d8a51344bf1d30f45d.png)
Ответы
Автор ответа:
0
(х-3)^4 - 5(х-3)^2 + 6 = 0
Пусть (х-3)^2 = а, тогда (х-3)^4 = а^2
а^2 - 5а + 6 = 0
по теореме Виета
а1= 2 а2=3
получим 2 новых уровнения
(х-3)^2 = 2 (х-3)^2 = 3
×^2 - 6х + 9 = 2 х^2 - 6х + 9 = 3
х^2 - 6х + 7 = 0 х^2 - 6х + 6 = 0
D= b^2 - 4ac= D=b^2 - 4ac=
=36 - 168= - 132 = 36 - 144 = - 108
-132 <0 корней нет -108 <0 корней нет
Пусть (х-3)^2 = а, тогда (х-3)^4 = а^2
а^2 - 5а + 6 = 0
по теореме Виета
а1= 2 а2=3
получим 2 новых уровнения
(х-3)^2 = 2 (х-3)^2 = 3
×^2 - 6х + 9 = 2 х^2 - 6х + 9 = 3
х^2 - 6х + 7 = 0 х^2 - 6х + 6 = 0
D= b^2 - 4ac= D=b^2 - 4ac=
=36 - 168= - 132 = 36 - 144 = - 108
-132 <0 корней нет -108 <0 корней нет
Похожие вопросы
Предмет: Математика,
автор: lilalisa443
Предмет: Английский язык,
автор: zhuktaia
Предмет: Физика,
автор: tevyh
Предмет: Математика,
автор: elina108
Предмет: Алгебра,
автор: kerimovvv